PROBLEMS OF KNOWLEDGE IN HUMAN SCIENCES. - Mejía Navarrete, Julio (2014)
The paper aims to examine the particular style of qualitative research as a way of approaching reality from the actual specific people and offers a closer perspective to humans. Central aspects of how qualitative research are rarely discussed explicitly, as interested in pointing out the theoretical questions and methodological problems of qualitative study. It is also presented the procedures to design and develop the qualitative research project.